Characterization of the pigment fraction in sweet bell peppers (Capsicum annuum L.) harvested at green and overripe yellow and red stages by offline multidimensional convergence chromatography/liquid chromatography–mass spectrometry. Issue 17 (6th September 2016) - Bonaccorsi, Ivana; Cacciola, Francesco; Utczas, Margita; Inferrera, Veronica; Giuffrida, Daniele; Donato, Paola; Dugo, Paola; Mondello, Luigi
Abstract : Offline multidimensional supercritical fluid chromatography combined with reversed‐phase liquid chromatography was employed for the carotenoid and chlorophyll characterization in different sweet bell peppers ( Capsicum annuum L.) for the first time. The first dimension consisted of an Acquity HSS C18 SB (100 × 3 mm id, 1.8 μm particles) column operated with a supercritical mobile phase in an ultra‐performance convergence chromatography system, whereas the second dimension was performed in reversed‐phase mode with a C30 (250 × 4.6 mm id, 3.0 μm particles) stationary phase combined with photodiode array and mass spectrometry detection. This approach allowed the determination of 115 different compounds belonging to chlorophylls, free xanthophylls, free carotenes, xanthophyll monoesters, and xanthophyll diesters, and proved to be a significant improvement in the pigments determination compared to the conventional one‐dimensional liquid chromatography approach so far applied to the carotenoid analysis in the studied species. Moreover, the present study also aimed to investigate and to compare the carotenoid stability and composition in overripe yellow and red bell peppers collected directly from the plant, thus also evaluating whether biochemical changes are linked to carotenoid degradation in the nonclimacteric investigated fruits, for the first time.